Advanced Materials for Water Treatment - Yuchen, Wu (Université d'Ottawa / University of Ottawa, 2019)
Access to fresh water has become one of the most urgent global issues because of growing fresh water consumption and wastewater emission. To treat this wastewater and increase the clean and sustainable water supply, there is a growing need for the development of advanced materials for water treatment. In this thesis, two research projects aimed at developing advanced materials for water treatment were conducted: i) the synthesis of an advanced magnetic flocculant for highly efficient solid suspension removal, and ii) the creation of advanced electrode materials for capacitive deionization (CDI). An introduction to the global water crisis is presented in Chapter 1, along with the concepts of magnetic flocculant and CDI, the thesis objective, strategies, novelties, and the research outline. The literature review of magnetic flocculants and CDI electrode materials is discussed in Chapter 2. Several general material synthesis methods and characterization methods related to this thesis are discussed in Chapter 3. In Chapter 4, details regarding the synthesis and use of the magnetic Fe3O4-graphene oxide (Fe3O4-GO) nanocomposite for rapid flocculation of solid suspended particles in wastewater and natural water are presented. In Chapter 5, the development of a three-dimensional ordered mesoporous titanium nitride (3DOM-TiN) is presented as a next generation high-performance non-carbon CDI electrode material, with further in-depth studies revealing its novel dual adsorption mechanism. In Chapter 6, a first-ever synthesis of a nanocomposite electrode of nitrogen-doped graphene-titanium oxynitride (NG-TiOxNy) for highly efficient CDI is presented. Detailed material synthesis methods, physiochemical and electrochemical characterization, adsorption analysis, electrosorption mechanism analysis, and CDI performance analysis can also be found in each chapter. Chapter 7 summarizes the work in Chapter 4-6. Additionally, several proposals and suggestions for future research are presented in Chapter 7. Supplemental information and preliminary experiments of Chapter 4-6 are given in the Appendix section.
Keywords: Material; Water-treatment; Magnetochemistry; Electrochemistry